2016 24th Signal Processing and Communication Application Conference (SIU) 2016
DOI: 10.1109/siu.2016.7495697
|View full text |Cite
|
Sign up to set email alerts
|

A novel biometric approach to generate ROC curve from the Probabilistic Neural Network

Abstract: The aim of this paper is to present a new method to produce a Receiver Operating Characteristic (ROC) curve from a Probabilistic Neural Network (PNN). Traditionally, an ROC curve has been used widely to report the recognition system measurements. Two main problems arise when using the PNN. Firstly, the PNN outputs are always logical (zeros and one); secondly, a PNN is considered as a multi-class classifier, because it usually has more than one output class. To solve these problems, we suggest a new approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Furthermore, a new feature extraction method named the Image Feature Enhancement (IFE) was adopted. In 2016, Al-Nima et al [30] suggested a novel approach to establish the Receiver Operating Characteristic (ROC) graph from an Artificial Probabilistic Neural Network (APNN) by employing the FT characteristic. Three feature extraction methods were examined: the Local Binary Pattern (LBP) with a statistical calculation method called the Coefficient of Variance (CV), the Gabor filter with the CV and the statistical CV computations alone in order to present the accuracy of the suggested approach.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, a new feature extraction method named the Image Feature Enhancement (IFE) was adopted. In 2016, Al-Nima et al [30] suggested a novel approach to establish the Receiver Operating Characteristic (ROC) graph from an Artificial Probabilistic Neural Network (APNN) by employing the FT characteristic. Three feature extraction methods were examined: the Local Binary Pattern (LBP) with a statistical calculation method called the Coefficient of Variance (CV), the Gabor filter with the CV and the statistical CV computations alone in order to present the accuracy of the suggested approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(5) It has been cited that using CV calculations can provide effective descriptions for the variances of the featured images. The resulting images have been partitioned into non-overlapping windows with a fixed size of 5 × 5 and the CV value is computed for each window [20,29,30,33]. To calculate the CV values, the following equations have been exploited [34]:…”
Section: Roi Of Middlementioning
confidence: 99%
See 3 more Smart Citations